Self-medication practices with antibiotics and associated factors among the public of Malaysia: a cross-sectional study - Aslam, Adeel; Zin, Che Suraya; Ab Rahman, Norny Syafinaz; Gajdács, Márió; Ahmed, Syed Imran; Jamshed, Shazia Qasim (Dove Medical Press, 2021)
Background: Self-medication with antibiotics (SMA) is an important public health issue, which can result in the facilitated development of antibiotic resistance, and may increase the risk of inappropriate utilization of antibiotics. So, the objective of the present study was to estimate the prevalence rate of SMA and to also explore SMA practices among the lay population of Kuala Lumpur (Malaysia). Methods: The current study was cross-sectional population-based and used a convenient sampling technique. Moreover, Lorenz’s formula was used to calculate the sample size and the required sample size was 480. Data were collected through face-to-face interviews with a pre-validated questionnaire and the study was conducted in Kuala Lumpur (Malaysia). Descriptive statistics, cross-tabulation, and logistic regression were executed by using SPSS version 24. Results: Out of 480 participants, 45.8% were polled male and the prevalence of SMA in this study was found to be 15.1%. The majority of participants 23.1% indicated that they practiced antibiotics at least once in the last six months. The commonly self-medicated antibiotics were amoxicillin-clavulanate 20.6%, ampicillin/cloxacillin 14.2%, and levofloxacin 8.3%. Moreover, 64.8% of participants indicated that they bought their antibiotics from pharmacies. Whereas, most of the participants practice antibiotics to save money 19.2% and time 23.1%. Findings from multivariate logistic regressions showed that predictors of SMA were male gender, (95% CI: 0.300–0.877) occupation (95% CI: 0.122–10.797), health insurance (95% CI: 0.025–0.472), and education (95% CI: 0.084–0.800). Conclusion: The results of this study indicate that SMA persists among the community and education level has a significant impact on this behavior. Thus, concerning health management authorities should step in with developing legislation to stop this practice, and by implementing such interventions and policies to educate and to raise awareness about the risk of SMA for the future.